Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2174/1874450801206010006
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Cetacean Fauna of the Mediterranean Levantine Basin

Abstract: Abstract:The Levantine Basin (LB) is still considered a void as regards its cetacean fauna: species population abundance and distribution patterns are unknown, and even the list of species and their regional status have so far not been finalized. In an effort to fill the knowledge gap, we present original data collected in the LB over the years [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009]. The data relies on strandings, bycatch victims and on incidental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
(44 reference statements)
2
20
0
Order By: Relevance
“…Currently, records of this species are documented in the Pelagos Sanctuary, near Lampedusa Island and in the Messina Strait [13], off western Sardinia [24], in the Cap Bon area (northern Tunisia) [25], in the eastern Ionian Sea [15], in the Aegean Sea [26][27][28], and in the Levantine Sea [29,30]. Local abundance estimates of this species have only been provided for long-term monitored areas such as the Alborán Sea [4,11], the waters off Malta [31], the Inner Ionian Sea Archipelago [6,32,33], the Gulf of Corinth [17,18,34], and the Thracian Sea [35].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, records of this species are documented in the Pelagos Sanctuary, near Lampedusa Island and in the Messina Strait [13], off western Sardinia [24], in the Cap Bon area (northern Tunisia) [25], in the eastern Ionian Sea [15], in the Aegean Sea [26][27][28], and in the Levantine Sea [29,30]. Local abundance estimates of this species have only been provided for long-term monitored areas such as the Alborán Sea [4,11], the waters off Malta [31], the Inner Ionian Sea Archipelago [6,32,33], the Gulf of Corinth [17,18,34], and the Thracian Sea [35].…”
Section: Introductionmentioning
confidence: 99%
“…This compares to 6.6 per 1000km in the eastern Mediterranean (19 strandings between 1993–2009 in Israel: 7 Cuvier's beaked whales, 4 minke whales, 4 fin whales, 3 sperm whales, 1 false killer whale; Kerem et al . 2012). Many of these are, however, caused by humans (e.g.…”
Section: Ancient Whale Exploitation In the Mediterranean?mentioning
confidence: 99%
“…in different locations across the Mediterranean coast of Israel. Later Kerem et al (2012) reported that it was most likely a member of the plumbea-type Indo-Pacific humpback dolphin.…”
Section: Introductionmentioning
confidence: 99%